Plasma Process. Polym. 12∕2013. Issue 12 (December 2013) - Mastanaiah, Navya; Banerjee, Poulomi; Johnson, Judith A.; Roy, Subrata
<x xml:space="preserve">Abstract</x> Cover: Dielectric Barrier Discharge (DBD) plasma devices are known ozone generators. The role of produced ozone in DBD sterilization was studied by examining its lethality to Escherichia coli. Measuring the levels of ozone produced during and after plasma generation identifies three phases: production, diffusion and decay. Each of these phases is characterized by an empirical formula. A correlation between the ozone production and the input energy flux to the plasma devices is also developed that is key to surface plasma sterilization. Further details can be found in the article by Subrata Roy et. al. on page 1120. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>